Case Report of Coronavirus Disease 2019 (COVID-19) in Patients with Pulmonary Tuberculosis and Sequelae Tuberculosis Accompanied by Malnutrition - Pakpahan, Edwin Anto; Ahmad, Diwa Aulia (Buletin Farmatera, 2022)
Abstract: Tuberculosis (TB) is an infectious chronic infectious disease caused by rod-shaped bacteria or bacillus, and is acid-resistant to Mycobacterium tuberculosis. Coronavirus disease (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Clinical manifestations of COVID-19 and tuberculosis include fever, cough, tightness, weight loss, weakness, and expectoration. Patients with tuberculosis have two times the risk of dying or experiencing severe symptoms. The case report reported one case of a 20-year-old man suffering from TB who had undergone 2nd line tuberculosis treatment and also suffered from a COVID-19 infection and malnutrition.Keywords: COVID-19, tuberculosis, malnutrition